2013
DOI: 10.3390/pathogens2020232
|View full text |Cite
|
Sign up to set email alerts
|

Host-Viral Interactions: Role of Pattern Recognition Receptors (PRRs) in Human Pneumovirus Infections

Abstract: Acute respiratory tract infection (RTI) is a leading cause of morbidity and mortality worldwide and the majority of RTIs are caused by viruses, among which respiratory syncytial virus (RSV) and the closely related human metapneumovirus (hMPV) figure prominently. Host innate immune response has been implicated in recognition, protection and immune pathological mechanisms. Host-viral interactions are generally initiated via host recognition of pathogen-associated molecular patterns (PAMPs) of the virus. This rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 196 publications
(267 reference statements)
0
31
0
Order By: Relevance
“…Viral-infection-induced immune response via pattern recognition receptors (PRRs) (TLRs and RIG-I-like receptors) (41,42) leads to activation of transcription factors, such as NF-B and IRFs, resulting in induction of proinflammatory cytokines and IFNs (43). The signaling cascade downstream of RIG-I includes activation of the IKK-related kinase IKK␣/␤ and TBK-1, resulting in phosphorylation of IRFs (IRF3 and IRF7).…”
Section: Discussionmentioning
confidence: 99%
“…Viral-infection-induced immune response via pattern recognition receptors (PRRs) (TLRs and RIG-I-like receptors) (41,42) leads to activation of transcription factors, such as NF-B and IRFs, resulting in induction of proinflammatory cytokines and IFNs (43). The signaling cascade downstream of RIG-I includes activation of the IKK-related kinase IKK␣/␤ and TBK-1, resulting in phosphorylation of IRFs (IRF3 and IRF7).…”
Section: Discussionmentioning
confidence: 99%
“…These cells also play a critical role in innate immunity, responding to microbial challenge and producing elevated levels of various cytokines that contribute to host innate defenses (Locati, Mantovani and Sica, 2013, Zanoni and Granucci, 2012, Striz, Brabcova, Kolesar and Sekerkova, 2014, den Haan and Kraal, 2012). These cells recognize and respond to microbial structures using pathogen-associated molecular patterns (PAMPs/MAMPs), which decorate the surface of the macrophage enabling uptake of antigenic components and triggering activation and phenotype plasticity after engagement of microbial or viral pathogens as ligands (Papadopoulos, Weinberg, Massari, Gibson, Wetzler, Morgan and Genco, 2013, Kolli, Velayutham and Casola, 2013, Salomao, Brunialti, Rapozo, Baggio-Zappia, Galanos and Freudenberg, 2012). As such in the gene expression patterns evaluated, TLR2 and TLR4 were both up-regulated in aged healthy tissues and in particular in aged periodontitis tissues, consistent with increases in the M1 phenotype of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used epithelial cells such as HEK293T and HeLa, which are very susceptible to viral replication. It was recently reported that HEK293T (Graham et al, 2014) and HeLa (Kolli et al, 2013) cells have fewer PRRs than Tolllike receptors (TLRs). This finding means that an aqueous extract of Angelica tenuissima Nakai may contain active components that can bind or penetrate the cell membrane.…”
Section: Discussionmentioning
confidence: 99%